CHERNOBYL ACCIDENT IN THE PUBLICATIONS OF THE OFFICIAL PERIODICALS OF DUBROVITSYA DISTRICT OF RIVNE REGION - Боруль, Н.В. (Science-based technologies, 2014)
The information on problems caused by the Chernobyl accident, accumulated during a period of twenty-five years and published in two official periodicals of investigated district, has been considered. Consequences of the Chernobyl accident for the population of Dubrovitsya district of Rivne region through their systematization in blocks, reflecting the main problems caused by the accident, have been analyzed. Considering a considerable socio-political resonance of the problems generated by the Chernobyl accident, in the first block the analysis of publications, in which socio-political aspects of problems of the postchernobyl period for the population of the studied area are highlighted, has been conducted. In the second block publications on Chernobyl issues, connected with ecological consequences of the Chernobyl accident for the Dubrovitsya district of Rivne region have been considered. In the third block the publications devoted to a health status of the population affected by the Chernobyl accident in the district under study have been analyzed.